Network Intrusion Detection with Constraints - Salgueiro, Pedro (2022)
In this work we present NeMODe a declarative system for Computer Network Intrusion detection providing a declarative Domain Specific Language for describing computer network intrusion signatures that can spread across several network packets, which allows to state constraints over network packets, describing relations between several packets. NeMODe provides several back-end detection mechanisms relying on Constraint Programming (CP) methodologies to find those intrusions.